(untitled) (Wire Insights: Journal of Innovation Insights, 2023)
Research writing is a great way for high school students to explore topics that they are interested in, discover information, and expand their research skills. However, there are challenges met by the teachers in teaching practical research that may vary from the essentials of writing. The study utilized mix method action research wherein it was subjected to one-group pretest-posttest design (quantitative) and thematic analysis on the lived experiences of participants as they go through the intervention (qualitative). The PROJECT ECHO initiative was helpful to practical research students as it enhances their writing skills. It was clearly manifested with the results of the paired t – test on before and after the intervention with established alpha error and degrees of freedom to produce critical value, the computed R value of 0.198 was less than the critical value of .273. This was interpreted to accept the null hypothesis. Momentarily, after the intervention, computed T value (3.785) was greater than that of the critical value (2.009), which afforded to reject the null hypothesis. This signifies that there was a significant difference between the pre and post – assessments of the writing skills of the practical research students before and after the intervention. As to the live experiences of the students on this initiative, the participants boarded on the relevance of exit slip as a way meaningful for writing skills enhancement.